END TO END LEARNING FOR A DRIVING SIMULATOR - V. F. Alexeev; A. I. Staravoitau; G. A. Piskun; D. V. Likhacheuski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Convolutional network approach is utilized for training an end-to-end model that would let a car drive itself around the track in a driving simulator by predicting steering angles based on the simulated camera data.